Los Invisibles : a History of Male Homosexuality in Spain. - Cleminson, R. (Iberian and Latin American studies., 2011)
Examining the social, medical and cultural history of male homosexuality in Spain, this book looks at it from the time homosexuality came to be an issue of medical, legal and cultural concern.